2019
DOI: 10.1155/2019/1278579
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Sleep Patterns and Self-Reported Academic Performance among Medical Students at the University of Ghana School of Medicine and Dentistry

Abstract: Background. Sleep habits and problems play a vital role in determining sleep quality. We describe sleep habits and problems among medical students and assess their possible effect on self-reported academic performance. Methods. We conducted a cross-sectional study among medical students at the University of Ghana during the 2014/2015 academic year. Data was collected using the Pittsburgh Sleep Quality Index (PSQI), a self-report questionnaire that assesses sleep quality over a 1-month time interval. Results. 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
51
2
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(67 citation statements)
references
References 36 publications
7
51
2
7
Order By: Relevance
“…In the present study, 30.9% participants reported sleep deprivation and the reason for inadequate sleep were the use of mobile phone, media, and friends among 71.4% participants and for 42% participants reported that it was due to study and stress. These results are in line with other studies[ 16 22 23 ], which reported the use of mobile and stress were the major factors for disturbed sleep pattern among budding health care professionals. Study shows that disturb sleep pattern may result in depression, anxiety, improper interpersonal relationship, poor academic performance, and more vulnerability to substance abuse.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the present study, 30.9% participants reported sleep deprivation and the reason for inadequate sleep were the use of mobile phone, media, and friends among 71.4% participants and for 42% participants reported that it was due to study and stress. These results are in line with other studies[ 16 22 23 ], which reported the use of mobile and stress were the major factors for disturbed sleep pattern among budding health care professionals. Study shows that disturb sleep pattern may result in depression, anxiety, improper interpersonal relationship, poor academic performance, and more vulnerability to substance abuse.…”
Section: Discussionsupporting
confidence: 93%
“…Study shows that disturb sleep pattern may result in depression, anxiety, improper interpersonal relationship, poor academic performance, and more vulnerability to substance abuse. [ 16 22 ] Therefore, reorganization, appropriate counseling, better planning, and support is needed and should be provided to students who are suffering from disturb sleep pattern.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Lemma et al [84] found a strong correlation of the symptoms of depression and anxiety with sleep quality. Poor sleep quality was also found to be associated with poor academic performance among medical students [85].…”
Section: Predictors Of Anxietymentioning
confidence: 94%
“…For instance, Lemma et al [81] found a strong correlation of the symptoms of depression and anxiety with sleep quality. Poor sleep quality was also found to be associated with poor academic performance among medical students [82].…”
Section: Predictors Of Anxietymentioning
confidence: 94%